Methodologies for developing information systems: a historical perspective - Avison, David (2006)
For the past 30 years and more, Information Systems Development (ISD) has been at the heart of the study and practice of Information Systems (IS). This paper examines the history of ISD methodologies and looks at some of the trends and issues concerning ISD, and shows how these have been reflected in methodologies and how organizations use (or do not use) them. Discussion of the present state of the field is followed by a discussion of possible future directions.